2009
DOI: 10.1080/13547500902825274
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variant ofCCND1: Association with HPV-mediated cervical cancer in Indian population

Abstract: The potential association of single nucleotide polymorphisms (SNPs) (G870A and G1722C) of CCND1 with susceptibility to cervical cancer was investigated. The study included 200 cervical cancer cases along with an equal number of healthy controls. Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis and direct sequencing were employed for genotyping. We found that women carrying the 870AA genotype have a 2.49-fold increased risk for the development of cervical cancer (odds ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 20 publications
1
25
1
Order By: Relevance
“…It was proposed that DNA-damaged cells in individuals with the A allele may bypass the G1/S checkpoint, leading to an increased proportion of cells with DNA damage and genetic alterations (Betticher et al, 1995). Meanwhile, epidemiological studies have reported an association between the CCND1 A/A genotype and increased risk of various cancers, including cervical (Jeon et al, 2005;Satinder et al, 2008;Thakur et al, 2009) and colorectal cancer (Ho-Pun-Cheung et al, 2007;Talseth et al, 2008;Tan et al, 2008). Although some studies have attempted to link this polymorphism with esophageal cancer, the results are often not reproducible.…”
Section: Introductionmentioning
confidence: 86%
“…It was proposed that DNA-damaged cells in individuals with the A allele may bypass the G1/S checkpoint, leading to an increased proportion of cells with DNA damage and genetic alterations (Betticher et al, 1995). Meanwhile, epidemiological studies have reported an association between the CCND1 A/A genotype and increased risk of various cancers, including cervical (Jeon et al, 2005;Satinder et al, 2008;Thakur et al, 2009) and colorectal cancer (Ho-Pun-Cheung et al, 2007;Talseth et al, 2008;Tan et al, 2008). Although some studies have attempted to link this polymorphism with esophageal cancer, the results are often not reproducible.…”
Section: Introductionmentioning
confidence: 86%
“…As shown in Table 3, 4 original and independent studies were analyzed (Catarino et al 2005;Satinder et al 2008;Jeon et al 2005;Thakur et al 2009), in addition to our data. Most subjects in the eligible studies were Asian, and all studies noted that the genotypic distribution among control subjects were consistent with the Hardy-Weinberg equilibrium.…”
Section: Meta-analysismentioning
confidence: 99%
“…Recent studies have shown that the G870A polymorphism is associated with elevated risks for breast, ovarian, and endometrial cancer (Ceschi et al 2005;Dhar et al 1999;Kang et al 2005). Also, several molecular epidemiological studies have examined the association between the G870A polymorphism of CCND1 and cervical cancer risk (Catarino et al 2008;Catarino et al 2005;Satinder et al 2008;Jeon et al 2005;Thakur et al 2009), but their results were inconclusive. No study has investigated the relation between the G870A polymorphism of CCND1 and cervical cancer in Chinese populations.…”
Section: Introductionmentioning
confidence: 98%
“…It was mentioned in one study that polymorphisms in predicted miRNA binding sites are likely to be deleterious; they are candidates for causal variants of human disease [32]. In our previous study, we showed that CCND1 gene SNP (rs678653) might provide some protection against the development of cervical cancer in Indian population [26].…”
Section: Resultsmentioning
confidence: 99%
“…Previously we have reported a potential protective effect of the CCND1 SNP G/C1722 (rs678653) on 3'UTR in cervical cancer susceptibility in Indian population [26]. Jiang et al [27] recently, published a report concerning the role of miRNAs which target CCND1, but they have not included the association of any CCND1 SNP in their study.…”
Section: Prediction Of Functional Effect Of Ccnd1 Snp (Rs678653)mentioning
confidence: 99%